2010
DOI: 10.1016/j.physc.2010.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic magnetotransport of superconducting and normal state in an electron-doped Nd1.85Ce0.15CuO4−δ single crystal

Abstract: The anisotropic properties of an optimally doped Nd1.85Ce0.15CuO 4−δ single crystal have been studied both below and above the critical temperature Tc via the resistivity measurement in magnetic field H up to 12 T. By scaling the conductivity fluctuation around the superconducting transition, the upper critical field Hc2(T ) has been determined for field parallel to the c-axis or to the basal ab-plane. The anisotropy factor γ = H ab c2 /H c c2 is estimated to be about 8. In the normal state (50 ≤ T ≤ 180 K), t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…By studying the behavior of the H field near T c , the in-plane and out-of-plane coherence lengths ξ ab and ξ c and the anisotropy factor γ were estimated. It results that ξ ≈ 20 c Å and ξ ≈ 100 ab Å, in agreement with the values reported in the literature [16,17], whereas, γ, evaluated as ∥ H c2 ab/ ∥ H c2 c, is quite large, around 30. As reported elsewhere [16], this value strongly depends on the crystalline quality of the compound, then also the oxygenʼs distribution into the NCCO structure can contribute to its anisotropy.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…By studying the behavior of the H field near T c , the in-plane and out-of-plane coherence lengths ξ ab and ξ c and the anisotropy factor γ were estimated. It results that ξ ≈ 20 c Å and ξ ≈ 100 ab Å, in agreement with the values reported in the literature [16,17], whereas, γ, evaluated as ∥ H c2 ab/ ∥ H c2 c, is quite large, around 30. As reported elsewhere [16], this value strongly depends on the crystalline quality of the compound, then also the oxygenʼs distribution into the NCCO structure can contribute to its anisotropy.…”
Section: Resultssupporting
confidence: 91%
“…A discrete number of papers have been dedicated to the study of transport and magnetic properties in electron-doped copper oxide superconductors [1][2][3][4][5][6], whereas very few studies have been carried out about their pinning properties [7,8]. Nevertheless, this kind of investigation is very important in defining the possible applications of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…The above method is thus not applicable in electron-doped ones. A scaling of the fluctuation conductivity σ flu (H, T) has been used to extract H c2 (T) [160][161][162][163]. In this method, the σ flu was obtained by subtracting the extrapolated normal state conductivity from the total conductivity.…”
Section: Multiband Superconductivitymentioning
confidence: 99%
“…Huge experiments have revealed that the FeSCs belong to a family with an unconventional pairing mechanism within FeAs(Se) layers. Information regarding the upper critical field H c2 and its anisotropy in superconductivity can be used as a fingerprint to understand the unconventional superconducting mechanism and to promote practical applications [2][3][4]. In addition, bidimensionality, which is represented by a rather high anisotropy between the ab-plane and c axis, is believed to be a very important factor for the occurrence of strong correlation physics and even high-T c superconductivity [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%